2015
DOI: 10.1371/journal.pone.0120402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bovine Parathyroid Hormone Withdrawal on MC3T3-E1 Cell Proliferation and Phosphorus Metabolism

Abstract: Hypocalcemia and hypophosphatemia are common complications after parathyroidectomy (PTX). Sudden removal of high circulating levels of parathyroid hormone (PTH) causes decreased osteoclastic resorption resulting in a decreased bone remodeling space. These phenomena are likely due to an increased influx of calcium and phosphorus into bone. However, there are currently no data to support this hypothesis. In this study, we found that PTX significantly reduced levels of PTH, calcium and phosphate. Compared with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
2
7
1
Order By: Relevance
“…The incidence of HBS in our cohort was high, probably because of high preoperative serum iPTH concentrations (median, 2237 pg/mL) and a large percentage reduction in immediate postoperative iPTH concentrations (median, 92.5%). This finding might be explained by a net calcium translocation from the extracellular fluid into bone due to a precipitous fall in PTH concentration after a prolonged period of PTH exposure, which has been confirmed by a previous in vitro study [31]. Furthermore, this finding supports a previous hypothesis that a sudden decrease in serum PTH concentrations after sustained elevation following parathyroidectomy results in the unopposed action of osteoblasts and massive influx of calcium into bone, thereby causing severe hypocalcemia.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of HBS in our cohort was high, probably because of high preoperative serum iPTH concentrations (median, 2237 pg/mL) and a large percentage reduction in immediate postoperative iPTH concentrations (median, 92.5%). This finding might be explained by a net calcium translocation from the extracellular fluid into bone due to a precipitous fall in PTH concentration after a prolonged period of PTH exposure, which has been confirmed by a previous in vitro study [31]. Furthermore, this finding supports a previous hypothesis that a sudden decrease in serum PTH concentrations after sustained elevation following parathyroidectomy results in the unopposed action of osteoblasts and massive influx of calcium into bone, thereby causing severe hypocalcemia.…”
Section: Discussionsupporting
confidence: 87%
“…A large amount of circulating calcium ions are then transferred to the bone to participate in osteogenesis. Thereafter, the serum calcium level declined after PTX, which was confirmed in a previous in vitro study [ 38–41 ]. Based on the results of this meta-analysis, it was concluded that a high preoperative iPTH level was a risk factor for postoperative hypocalcemia.…”
Section: Discussionsupporting
confidence: 82%
“…The typical characteristic of fluorine toxicity includes mottling and pitting of teeth and enlargements on the shafts of long bones. In the present study, fluorine contents in soil and herbage were lower than the critical contents of 30 to 40 ppm (Adedokun and Adeol, 2013;Liu et al, 2015;Burk et al, 2015). The fluorine contents in blood and hair were within the healthy range, therefore, the illness of the Tibetan gazelle was not related to fluorosis.…”
Section: Discussioncontrasting
confidence: 52%